A rare case report of panuveitis with retinochoroidal involvement, retinitis, and retinal vasculitis due to extensive tinea corporis - Konana, Vinaya Kumar; Babu, Kalpana (Frontiers in Ophthalmology, 2023)
A 40-year-old Asian Indian woman, diagnosed as having idiopathic panuveitis (elsewhere) 3 years earlier and being treated with oral steroids (20 mg/day) and methotrexate (25 mg/week), presented to us with worsening vision in both eyes. Her best corrected visual acuity (BCVA) was perception of light in her right eye and counting fingers close to face in her left eye. A slit lamp examination showed an anterior chamber (AC) reaction (1+) in both eyes with posterior synechia, a total cataract in her right eye, and pseudophakia in her left eye. The left fundus showed vitritis, vitreous membranes, chorioretinitis, multifocal areas of retinitis, and retinal vascular sheathing. A systemic examination showed extensive multifocal areas of tinea corporis on the hands and torso. Owing to the leukocytosis (22,000 cells/mm3), diagnostic vitrectomy was initially deferred and 100 mg of oral itraconazole was given twice a day for 3 months. The vitritis improved a little and her total white blood cell (WBC) count improved with treatment of the skin infection. Following a diagnostic vitrectomy later in her left eye, resolving areas of retinitis were seen. Complete resolution of eye inflammation was seen at the end of 6 weeks. At the 6-month follow-up, her BCVA was 6/18 in left eye and she was off oral steroids and methotrexate, with no recurrence of inflammation. We speculate a probable association between the ocular inflammation and extensive tinea corporis based on the therapeutic response to itraconazole.